At the margins of the international community, but inside global knowledge and policy flows? How cities in Taiwan and Scotland position themselves within intergovernmental rhetoric on nature-based solutions - Leslie Mabon (Nature-Based Solutions, 2023)
Nature-based solutions have significant interest as a response to environmental change in cites. There is a burgeoning field of research into how knowledge and expertise travels between cities to enable learning for and deployment of nature-based solutions and other climate and sustainability strategies. Yet, intergovernmental fora and institutions retain a key role in mediating these knowledge and policy flows. This paper evaluates how cities in countries distanced from state-level international platforms engage with global knowledge flows on nature-based solutions for climate adaptation, assessing Glasgow (Scotland) and New Taipei (Taiwan). Analysis of municipal adaptation plans and associated policies shows both Glasgow and New Taipei pro-actively adopt the language and metrics of international policies and strategies when justifying and assessing nature-based solutions, and use nature-based solutions as a means of furthering their aspirations for greater international recognition and engagement. Moreover, localisation of international best practices for nature-based solutions deployment offers an opportunity for cities such as Glasgow and New Taipei to attract global attention and position themselves as centres of expertise – regardless of the status of the country they are located in – in the global knowledge economy of urban nature-based climate adaptation.